Bibliometric analysis of Advanced Oxidation Processes studies with a focus on Life Cycle Assessment and Costs - Clímaco Cunha, Isadora Luiza; Machado, Pedro Gerber; de Oliveira Ribeiro, Celma; Kulay, Luiz (Environmental science and pollution research international, 2024)
Advanced oxidation processes (AOPs) are wastewater treatment technologies that stand out for their ability to degrade Contaminants of Emerging Concern (CECs). The literature has extensively investigated these removal processes for different aqueous matrices. Once technically mature, some of these systems have become accredited to be applied on a large scale, and therefore, their systemic performances in the environmental and cost spheres have also become essential requirements. This study proposed corroborating this trend, analyzing the available literature on the subject to verify how experts in the AOP area investigated this integration during 2015–2023. For this purpose, a sample of publications was treated by applying the Systematic Review (SR) methodology. This resulted in an extract of 83 studies that adopted life-cycle logic to estimate environmental impacts and process costs or evaluated them as complementary to the technical dimension of each treatment technology. This analysis found that both dimensions can be used for selecting or sizing AOPs at the design scale. However, the appropriate choice of the impact categories for the environmental assessment and establishing a methodology for cost analysis can make the approach still more effective. In addition, a staggering number of processes would broaden the reality and applicability of the estimates, and adopting multicriteria analysis methodologies could address essential aspects of decision-making processes during the design of the arrangements. By meeting the original purposes, the study broadened the requirements for designing AOPs and disseminating their use in mitigating the discharge of CECs.